2022
DOI: 10.3390/vaccines10071023
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic Targeting of NG2/CSPG4 in Solid Organ Cancers

Abstract: : Neuro-glia antigen 2/chondroitin sulfate proteoglycan 4 (NG2/CSPG4, also called MCSP, HMW-MAA, MSK16, MCSPG, MEL-CSPG, or gp240) is a large cell-surface antigen and an unusual cell membrane integral glycoprotein frequently expressed on undifferentiated precursor cells in multiple solid organ cancers, including cancers of the liver, pancreas, lungs, and kidneys. It is a valuable molecule involved in cancer cell adhesion, invasion, spreading, angiogenesis, complement inhibition, and signaling. Although the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Figs. S1 C; S3 E) [ 48 ], which is consistent with the characteristics reported in the literature [ 7 ]. However, whether NG2 + cells can generate multiple cell types is currently unclear.…”
Section: Discussionsupporting
confidence: 89%
“…Figs. S1 C; S3 E) [ 48 ], which is consistent with the characteristics reported in the literature [ 7 ]. However, whether NG2 + cells can generate multiple cell types is currently unclear.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, genetic mutation of CSPG4 led to the dysfunction of oligodendrocyte progenitor cells and failure to differentiate into myelinating oligodendrocytes in familial schizophrenia [ 15 ]. Recent studies have identified that NG2 functions in various cell types and NG2 levels are increased in many aggressive cancers, including melanomas [ 16 ], gliomas [ 17 ], mesotheliomas [ 18 ], sarcomas [ 19 ], anaplastic thyroid cancer [ 20 ], triple-negative breast cancers [ 21 ] and hepatocellular carcinoma [ 22 ]. Moreover, NG2 overexpression may induce highly aggressive tumors characterized by increased angiogenesis and a moderately invasive phenotype [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple therapeutic approaches such as surgical and operative excision, radiotherapy and chemotherapy have been applied in the treatment of this disease, the treatment effect is not satisfactory, which leads a poor prognosis [4]. Recently, a promising therapeutic strategy named as immunotherapy is pointed, and proves to be effective against solid organ cancers including HCC under laboratory conditions [5,6]. However, the well understanding of the changes in immune microenvironment during HCC is still urgent, which may contribute to identify novel and e cient Immunotherapeutic targets.…”
Section: Introductionmentioning
confidence: 99%